EFEKTIVITAS PROBLEM BASED LEARNING TERHADAP PEMBELAJARAN QIRA'AH MENGGUNAKAN KITAB AKHLAQUL BANAAT (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the low ability of students in understanding qira’ah texts, the use of conventional teaching methods, and the limited student engagement during learning activities, as reflected in the average pre-test score of 54.44 and the high need for more active learning reaching 85.03%. Based on these conditions, this study aims to determine the effectiveness of the Problem Based Learning (PBL) model in improving qira’ah skills using the book Akhlaqul Banaat at Pondok Pesantren Sabilul Muhtadin Banyuasin. This research employs a Mixed Method approach, combining quantitative and qualitative methods. Quantitative data were collected through pre-test, post-test, and student need and satisfaction questionnaires, while qualitative data were obtained through observation, interviews, and documentation to provide deeper insights into the learning process. The analysis of learning improvement was conducted using the N-Gain formula. The results show a significant increase in students’ qira’ah ability after the implementation of PBL, with the post-test average rising to 86.48 and an N-Gain value of 0.7640 or 76.40%, categorized as high and effective. Student satisfaction also showed a very positive response with a percentage of 87.78%. Qualitative findings further support that PBL encourages students to be more active, critical, and capable of understanding the content and moral messages in Akhlaqul Banaat more deeply. Therefore, PBL is proven to be effective in improving the quality of qira’ah learning in Islamic boarding school settings.